Study of Ube3a knockdown and expression in the in vitro system. - Ng, Xiang Wen. (2009)
Angelman syndrome (AS) is a neurological disorder which is caused by loss of maternally expressed genes on the human chromosome 15q11-q13 in the brain. AS patients show signs of mental retardation, seizures, lack of speech and ataxic gait. In this study, we would like to look into Ube3a, whose mutation or deletion caused AS, by performing Ube3a knockdown in P19 cell line and heat shock assay in cells. Ube3a knockdown cells showed reduction in both transcription and translation levels of the encoded protein, E6-AP. Increase in HSP70 mRNA levels was also observed in knockdown cells. Under heat stress condition, E6-AP was not found to be induced, unlike HSP70 whose expression increase dramatically. RNA obtained from knockdown cells will be used for microarray analysis to identify genes affected by lack of Ube3a expression in order to elucidate the molecular mechanisms of AS.